The role of the Zn/Nd ratio in the microstructural evolution of the Mg-Zn-Nd system during static recrystallization: Grain boundary partitioning of solutes. (June 2017) - Sanjari, M.; Farkoosh, A.R.; Shalchi Amirkhiz, B.; He, Y.; Javaid, A.; Kabir, A.S.; Su, J.; Jung, In-Ho; Yue, S.
Abstract: Microstructure evolution in Mg4Zn1Nd and Mg1Zn1Nd alloys was investigated after warm rolling and isothermal annealing. Transmission electron microscopy analysis revealed solute segregations at high-angle grain boundaries during annealing. The Nd concentration at the grain boundaries decreased with the increase of the Zn/Nd ratio. After a relatively long time of annealing (90 min), the grain boundaries of the Mg1Zn1Nd alloy were decorated with Nd- and Zn-containing precipitates, whereas in Mg4Zn1Nd, the precipitates were randomly distributed within the matrix. The kinetics of solute partitioning and precipitation were evaluated by thermodynamic calculations and linked to the recrystallization and grain growth. Graphical abstract: